Islamophobia as a Deterrent to Halal Global Trade. Issue 1 (1st October 2017) - Barbara Ruiz-Bejarano
Abstract : Islamophobia continues to be on the rise in Europe and other regions, such as Australia, Canada and the United States. It is now a global phenomenon which has multiple manifestations and is generated at different layers of society, and does not only affect citizens 1 in non-Islamic countries, but has recently shown a new expression: the target has shifted towards Islamic economies, and more specifically towards the halal trade. Emerging economies in the region of Asia-Pacific and the Gulf are net importers of halal products (particularly foodstuff), which, paradoxically, are produced in non-Islamic economies. A report commissioned by the Dubai government, and researched and written by Thompson Reuters and Dinar Standard, 2 valued the halal food and beverage (F&B) market at US 1.37 trillion in 2014. That represented 18.2% of the total global F&B market. In addition, the youthful population of the Muslim world - with 60% under the age of 30 - indicates that demand for halal products and services is likely to continue its upward growth curve and become an increasingly influential market over the next decade. This tremendously attractive market niche, combined with the slow growth of the economies of Europe, Canada, Australia and the United States, has prompted many industries to seek halal certification and to adapt their products and services to the requirements of Muslim consumers worldwide, including the significant minorities already living outside Islamic economies. 3 However, some newcomers to the halal global market have found that there is another obstacle to overcome, apart from those already present in global trade: Islamophobia. In this article, I will explore the many expressions of Islamophobia aimed at stopping the growth of the halal market, and the different policies and attitudes of governments and institutions when confronted with the need to balance economic growth with cultural misunderstandings and hatred. I found systematic attempts to undermine the halal food industry made by some European Members of Parliament, claims of animal cruelty sparked by animal rights groups, bans on halal sacrifice in the meat industry, the "boycott-halal" on-line campaign, alleged funding of terrorism, threats and other expressions of hatred that have managed to prevent many businesses from accessing the emerging halal market.